Analysis of the Use of Figurative Language in Taylor Swift's Song Lyrics - Rahmawati, Astri Rahayu (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
This study aims to describe the types of figurative language and connotative meanings contained in four Taylor Swift songs,